Enhanced sulfate formation in mixed biomass burning and sea-salt interactions mediated by photosensitization: effects of chloride, nitrogen-containing compounds, and atmospheric aging - R. Tang; R. Tang; J. Ma; R. Zhang; W. Cui; Y. Qin; Y. Chu; Y. Qin; A. L. Vogel; C. K. Chan (Atmospheric Chemistry and Physics)
Discrepancies persist between modeled simulations and measured sulfate concentrations in the marine boundary layer, especially when the marine air is influenced by biomass burning plumes. However, there has been a notable dearth of research conducted on the interactions between sea-salt aerosol and biomass burning plumes, impeding a comprehensive understanding of sulfate formation. This work studied sulfate formation by mixing real biomass burning (BB) extracts and NaCl, mimicking internal mixtures of BB and sea-salt particles. BB–NaCl particles had a significantly higher sulfate formation rate than incense burning (IS)–NaCl particles. For fresh particles, the sulfate formation rate followed the trend of corn straw (CS)–NaCl > rice straw (RS)–NaCl > wheat straw (WS)–NaCl > IS–NaCl. The filter sample aging was achieved by exposure to OH• generated from UV irradiation. After aging, RS–NaCl particles exhibited the highest enhancement in sulfate formation rates among all the BB–NaCl particles due to interactions between RS and NaCl. Bulk aqueous experiments spiked with NaCl using mixtures of model photosensitizers (PSs) and nitrogen-containing organic compounds (NOCs), pyrazine (CHN), and 4-nitrocatechol (CHON) revealed positive effects of chloride in the PS–CHON system and negative effects in the PS–CHN system in sulfate formation. Our work suggests that BB reaching or near coastal areas can affect sulfate formation via photosensitizer-mediated reactions, potentially exacerbating air pollution.